Requirements Association Extraction based on Use Cases Diagram - Gelu, Peter; Sarno, Riyanarto; Siahaan, Daniel (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 1 April 2018DO - 10.24843/LKJITI.2018.v09.i01.p02, 2018)
Requirements are the initial step in the software development process. It is very important to ensure the association (relationship) of requirements and high quality of specification as more than three-quarters failure of software derives from the software requirement process. Therefore, the analysis process is required to ensure the association between requirements and the requirements of other users. As a result, interdependency requirements association is essential. This research proposes an approach of software requirements association. These are based on the reference of interdependency in the user case, namely the result of collaboration of the association of the dependency of requirements based on Unified Modeling Language (UML) design in the Use cases diagram. In this research, the mapping between requirements and use cases and interdependencies between use cases are used to determine the interdependency between requirements. The analysis presented is the association of similar requirements, requires, or, temporal, e laborates dan g eneralises. The purpose of this r esearch is to generate a requirements dependency graph that models the type of dependency between requirements within a software project.